Pengaruh Pertumbuhan Pakcoy (Brassica chinensis L.) terhadap Perlakuan Konsentrasi Larutan Hidroponik Sistem NFT - Fitri Yulianti; Adinda Nurul Huda Manurung (Universitas Gunadarma, 2017)
Hydroponic is one of the future agricultural systems because it can becultivated in various places, whether in village, city, on open land or onapartment. NFT (Nutrient Film Technique) is a model of hydroponic cultivation by placing plant roots in a shallow water layer. Pak choi attracted by many people because pak choi rich in vitamin A, E, and K were beneficial for health. The purpose of this research was to know the effect of the growth of pak choi on the treatment of hydroponic nutrition solution concentration in NFT system. This research was conducted at F6 Campus Gunadarma University located at Depok from March to April 2017. The experiment design was arranged in Completely Randomized Design with one factor, that is the concentration of hydroponic solution (1050 ppm, 1200 ppm and 1400 ppm) with 5 replications. The Results were analyzed using analysis of variance (ANOVA) with 5% significant level. If it is significantly different, then further test was done by DMRT (Duncan’s Multiple Range Test). The results of this research indicated that the treatment of nutrient solution concentration did not affect the growth of pak choi such as plant height, number of leaves, root number, root length, weight per plant, crown weight per plant, root weight per plant, leaf surface area, leaf color and root color. The best treatment is 1050 ppm because with low concentrations of nutrient solution produced the same pak choi growth with other treatments